Katanin Effects on Dynamics of Cortical Microtubules and Mitotic Arrays in Arabidopsis thaliana Revealed by Advanced Live-Cell Imaging - Komis, George; Luptovčiak, Ivan; Ovečka, Miroslav; Samakovli, Despina; Šamajová, Olga; Šamaj, Jozef (Frontiers in Plant Science, 2017)
Katanin is the only microtubule severing protein identified in plants so far. Previous studies have documented its role in regulating cortical microtubule organization during cell growth and morphogenesis. Although, some cell division defects are reported in KATANIN mutants, it is not clear whether or how katanin activity may affect microtubule dynamics in interphase cells, as well as the progression of mitosis and cytokinesis and the orientation of cell division plane (CDP). For this reason, we characterized microtubule organization and dynamics in growing and dividing cotyledon cells of Arabidopsis ktn1-2 mutant devoid of KATANIN 1 activity. In interphase epidermal cells of ktn1-2 cortical microtubules exhibited aberrant and largely isotropic organization, reduced bundling and showed excessive branched microtubule formation. End-wise microtubule dynamics were not much affected, although a significantly slower rate of microtubule growth was measured in the ktn1-2 mutant where microtubule severing was completely abolished. KATANIN 1 depletion also brought about significant changes in preprophase microtubule band (PPB) organization and dynamics. In this case, many PPBs exhibited unisided organization and splayed appearance while in most cases they were broader than those of wild type cells. By recording PPB maturation, it was observed that PPBs in the mutant narrowed at a much slower pace compared to those in Col-0. The form of the mitotic spindle and the phragmoplast was not much affected in ktn1-2, however, the dynamics of both processes showed significant differences compared to wild type. In general, both mitosis and cytokinesis were considerably delayed in the mutant. Additionally, the mitotic spindle and the phragmoplast exhibited extensive rotational motions with the equatorial plane of the spindle being essentially uncoupled from the division plane set by the PPB. However, at the onset of its formation the phragmoplast undergoes rotational motion rectifying the expansion of the cell plate to match the original cell division plane. Conclusively, KATANIN 1 contributes to microtubule dynamics during interphase, regulates PPB formation and maturation and is involved in the positioning of the mitotic spindle and the phragmoplast.